The Impact of Perioperative Chemotherapy on Survival in Patients With Gastric Signet Ring Cell Adenocarcinoma - Maria João Monteiro de Almeida Baptista Barbosa (2021)
Background & Aims: Gastric cancer (GC) has a high incidence and high mortality rate. Currently, the standard of care in Europe for locally advanced GC is perioperative chemotherapy followed by surgical resection. However, not all types of GC respond equally to chemotherapy. Signet ring cell carcinoma (SRCC) shows higher rates of chemoresistance and its prognosis remains controversial. We aim to evaluate SRCC's response to perioperative chemotherapy and its impact on survival. Materials and Methods: We conducted a Unicenter transversal retrospective study including all patients submitted to perioperative chemotherapy followed by surgical resection between January 2010 and June 2020. Results: A total of 102 patients with a mean age (SD) of 62,8 (10,2) years were analyzed. No difference was found in the pre-chemotherapy tumor stage and histopathological response in both groups. SRCC showed higher rates of ganglionar invasion (median of 15,5 lymph nodes invaded vs. 3,5 lymph nodes invaded), lower rates of ganglionar regression (median of 33% vs. 46%), and higher rates of chemotherapy adverse effects. Mortality rates were higher in the SRCC group (42,2% vs 30,8%), but this presented no statistical significance. Conclusion: SRCC patients seemed to benefit slightly less from perioperative chemotherapy, therefore, we need to search for other treatment options for these patients.